Dual RNA-Sequencing of Eucalyptus nitens during Phytophthora cinnamomi Challenge Reveals Pathogen and Host Factors Influencing Compatibility - Meyer, Febé E.; Shuey, Louise S.; Naidoo, Sitha; Mamni, Thandekile; Berger, Dave K.; Myburg, Alexander A.; van den Berg, Noëlani; Naidoo, Sanushka (Frontiers in Plant Science, 2016)
Damage caused by Phytophthora cinnamomi Rands remains an important concern on forest tree species. The pathogen causes root and collar rot, stem cankers and dieback of various economically important Eucalyptus spp. In South Africa, susceptible cold tolerant Eucalyptus plantations have been affected by various Phytophthora spp. with P. cinnamomi considered one of the most virulent. The molecular basis of this compatible interaction is poorly understood. In this study, susceptible Eucalyptus nitens plants were stem inoculated with P. cinnamomi and tissue was harvested five days post inoculation. Dual RNA-sequencing, a technique which allows the concurrent detection of both pathogen and host transcripts during infection, was performed. Approximately 1% of the reads mapped to the draft genome of P. cinnamomi while 78% of the reads mapped to the Eucalyptus grandis genome. The highest expressed P. cinnamomi gene in planta was a putative crinkler effector (CRN1). Phylogenetic analysis indicated the high similarity of this P. cinnamomi CRN1 to that of Phytophthora infestans. Some CRN effectors are known to target host nuclei to suppress defense. In the host, over 1400 genes were significantly differentially expressed in comparison to mock inoculated trees, including suites of pathogenesis related (PR) genes. In particular, a PR-9 peroxidase gene with a high similarity to a Carica papaya PR-9 ortholog previously shown to be suppressed upon infection by Phytophthora palmivora was down-regulated two-fold. This PR-9 gene may represent a cross-species effector target during P. cinnamomi infection. This study identified pathogenicity factors, potential manipulation targets and attempted host defense mechanisms activated by E. nitens that contributed to the susceptible outcome of the interaction.